Structure-guided approaches to targeting stress responses in human fungal pathogens - LeBlanc, Emmanuelle V. (J Biol Chem, 2020)
Fungi inhabit extraordinarily diverse ecological niches, including the human body. Invasive fungal infections have a devastating impact on human health worldwide, killing ∼1.5 million individuals annually. The majority of these deaths are attributable to species of Candida, Cryptococcus, and Aspergillus. Treating fungal infections is challenging, in part due to the emergence of resistance to our limited arsenal of antifungal agents, necessitating the development of novel therapeutic options. Whereas conventional antifungal strategies target proteins or cellular components essential for fungal growth, an attractive alternative strategy involves targeting proteins that regulate fungal virulence or antifungal drug resistance, such as regulators of fungal stress responses. Stress response networks enable fungi to adapt, grow, and cause disease in humans and include regulators that are highly conserved across eukaryotes as well as those that are fungal-specific. This review highlights recent developments in elucidating crystal structures of fungal stress response regulators and emphasizes how this knowledge can guide the design of fungal-selective inhibitors. We focus on the progress that has been made with highly conserved regulators, including the molecular chaperone Hsp90, the protein phosphatase calcineurin, and the small GTPase Ras1, as well as with divergent stress response regulators, including the cell wall kinase Yck2 and trehalose synthases. Exploring structures of these important fungal stress regulators will accelerate the design of selective antifungals that can be deployed to combat life-threatening fungal diseases.